Semaphorin signaling in bone. (5th September 2016) - Verlinden, Lieve; Vanderschueren, Dirk; Verstuyf, Annemieke
Abstract: Semaphorin molecules regulate cell adhesion and motility in a wide variety of cell types and are therefore involved in numerous processes including axon guidance, angiogenesis, cardiogenesis, tumor growth, and immune response. Increasing evidence points to a role of transmembrane, membrane-associated and soluble semaphorins during bone development as well as in the control of normal bone homeostasis. Within bone, semaphorins are implicated in the communication between different cell types by relaying signals in an autocrine or paracrine way. Semaphorins are not only involved in bone resorption but also in bone formation. Therefore, targeting semaphorin-induced signaling in bone may constitute an interesting new therapeutic strategy in osteoporosis. However, all the pioneering research on semaphorins is performed in mice and it remains to be established to what extent semaphorin signaling pathways are conserved between mice and men. In addition, knowledge of semaphorin signaling in bone mostly arises from loss/gain of function studies of one single semaphorin and/or receptor. However, different semaphorin molecules are co-expressed in bone and their signaling pathways are likely to interact in a complex and coherent way that needs proper understanding before targeting semaphorin signaling can be therapeutically exploited. Highlights: Various semaphorin molecules and their neuropilin and plexin receptors are expressed in bone. Semaphorins are involved in bone development as well as in the control of normal bone homeostasis. Semaphorins affect communication between different cell types by relaying signals in an autocrine or paracrine way. Semaphorins target bone resorption as well as formation, making them interesting therapeutic targets.